Comparison of ST-segment resolution influencing in hospital outcome after primary percutaneous coronary intervention and fibrinolysis (with streptokinase) in patients with acute ST-segment elevation myocardial infarction - Rahman, Md. Hasanur; Afrin, Syeda Fahmida; Islam, Md. Aminul; Shahriar, Md. Saqif; Zahid, Md. Abu; Badiuzzaman, Mohammad (Bangladesh Journal of Medical Science, 2016)
Background: Coronary artery disease (CAD) is the most common cause of mortality & morbidity in all over the world. Reperfusion therapy is the cornerstone for treating acute ST-segment elevation myocardial infarction. Effective reperfusion in STEMI can be achieved by either fibrinolysis or primary percutaneous coronary intervention (PPCI). PPCI generally produces better outcomes than fibrinolysis but is not widely available. ST-segment abnormalities play a fundamental role in assessment and decision making for patients with STEMI. Methods: This quasi-experimental study was conducted in the Department of Cardiology, National Heart Foundation Hospital and Research Institute. Group I underwent primary PCI and group II received fibrinolytic therapy as reperfusion therapy for acute STEMI. Results: The mean ST-segment resolutions were significantly more in group I than group II at 60 minutes (63.54±20.98 vs 33.97±15.88%, p<0.001) and at 90 minutes (73.15±18.76 vs 60.06±23.33%, p<0.015). However the difference is not significant at 180 minutes after procedure (74.48±18.09 vs 65.33±21.20%, p=0.064). In our study we observed that significantly higher number of patients of group II developed acute LVF (33.3% vs 6.1%, p=0.005) and cardiogenic shock (18.2% vs 3.0%, p=0.046) than group I and Rescue PCI was needed in 5 (15.2%% vs 0%, p=0.020) patients of group II than group I. Conclusion: ST-segment resolution occurs earlier and more completely after Primary percutaneous coronary intervention than fibrinolysis (with Streptokinase) with better in hospital outcome in patients with acute STEMI. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.252-256